Beethoven's masterpieces ; [No. 1 of vol. 1 (op. 13)] : being the entire of his grand sonatas, for the piano forte edited by his friend and pupil Carl Czerny ... A new edition fingered and revised by Dr. Rahles. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Czerny, Carl, 1791-1857 (editor):::Contributor::::::::::::; Rahles, Dr.:::Contributor:::::::::::: (United Kingdom; R. Cocks & Co.; London, 2022)
Early edition of the Sonata no. 8 in C Minor, op. 13, edited by Carl Czerny and published by R. Cocks in London as no. 1 of the series "Beethoven's Masterpieces"; revised edition with fingerings by Dr. Rahles.